Determinants for Postnatal Care Utilization among Mothers in Dodoma Region, Tanzania: A Community-Based Cross-Sectional Study (Tanzania Medical Journal, 2023)
BackgroundPostnatal care (PNC) is concerned with preventive care, practices, and assessments designed to identify and manage maternal and newborn complications during the first six weeks after birth. It has been shown that proper management of life-threatening conditions soon after childbirth can prevent maternal and prenatal mortality and morbidity.ObjectiveThe objective of this study was to assess the determinants for postnatal care utilization among mothers in Dodoma Region, Tanzania.MethodsA cross-sectional study was conducted using a structured questionnaire from January to March 2021. A total of 420 postnatal mothers who were in the 7th to 12th weeks after childbirth were included in the study. Bivariate and multivariate logistic regression analysis was performed using SPSS version 26.0. An adjusted odds ratio with a 95% confidence interval and p-value less than 0.05 was applied.ResultsOnly 136 (32.2%) attended four postnatal care visits during their postnatal period as recommended. Regarding the timing of PNC visits, results showed that the majority of 330 (78.6%) participants received PNC service within the first 24 hours. However, 64 (15.2%) of participants attended PNC visits between 48 to 72 hours, while 7 (1.7%) between 7 - 14 days and 19 (4.5%) did not attend any PNC. After adjusting for the potential confounder in multivariate logistic regression, education level, place of residence, and mode of delivery remained the strong predictors of adequate PNC service uptake among study participants. Regarding educational level, participants with secondary education and above were 4 times more likely to use adequate PNC services compared to those with informal education (AOR=4.456; 95%CI =1.050-18.907; P=0.043). Participants residing in urban areas were almost 2 times more likely to utilize adequate PNC services compared to those living in a rural area (AOR=1.900;95%CI = 1.177- 3.067; P=0.009). Likewise, participants who delivered through C/Section were 30 times more likely to utilize the PNC services adequately compared to those with normal delivery AOR=29.515; 95%CI = 10.775- 80.844; P=0.001).Conclusion and recommendations The finding from this study indicated that the uptake of four postnatal care visits among mothers in the Dodoma region was low. Educational levels of a mother, place of residence, and mode of delivery were significant determinants for adequate utilization of PNC services. Considering this, it is necessary to create awareness of adequate utilization of PNC services, especially among women with low education and women in rural areas.